Effect of l-theanine on glutamatergic function in patients with schizophrenia. Issue 5 (21st April 2015) - Ota, Miho; Wakabayashi, Chisato; Sato, Noriko; Hori, Hiroaki; Hattori, Kotaro; Teraishi, Toshiya; Ozawa, Hayato; Okubo, Tsutomu; Kunugi, Hiroshi
Abstract : Objectives: Glutamatergic dysfunction in the brain has been implicated in the pathophysiology of schizophrenia. Previous studies suggested thatl -theanine affects the glutamatergic neurotransmission and ameliorates symptoms in patients with schizophrenia. The aims of the present study were twofold: to examine the possible effects ofl -theanine on symptoms in chronic schizophrenia patients and to evaluate the changes in chemical mediators, including glutamate + glutamine (Glx), in the brain by using 1 H magnetic resonance spectroscopy (MRS). Method: The subjects were 17 patients with schizophrenia and 22 age- and sex-matched healthy subjects.l -Theanine (250 mg/day) was added to the patients' ongoing antipsychotic treatment for 8 weeks. The outcome measures were the Positive and Negative Syndrome Scale (PANSS), Pittsburgh Sleep Quality Index scores and MRS results. Results: There were significant improvements in the PANSS positive scale and sleep quality after thel -theanine treatment. As for MRS, we found no significant differences in Glx levels before and after the 8 weekl -theanine treatment. However, significant correlations were observed between baseline density of Glx and change in Glx density byl -theanine. Conclusions: Our results suggest thatl -theanine is effective in ameliorating positive symptoms and sleep quality in schizophrenia. The MRS findings suggest thatl -theanine stabilises the glutamatergic concentration in the brain, which is a possible mechanism underlying the therapeutic effect.